2019
DOI: 10.15376/biores.14.4.7636-7654
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillated cellulose rheology: Effects of morphology, ethanol/acetone addition, and high NaCl concentration

Abstract: The effects of ethanol or acetone addition (2.5% to 40% w/w) and high ionic strength (50 mM to 1000 mM NaCl) on the rheology of carboxymethylated (NFC-carb) and 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) oxidized (NFC-TEMPO) nanofibrillated cellulose (NFC) suspensions were studied. Morphological characterization and centrifugation showed that NFC-TEMPO had a much finer overall morphology than NFC-carb. Rheological measurements were taken at 1.3 wt% using a stress-controlled rheometer equipped with cone and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Weaker hydrogen bonding interactions may result in fewer molecular entanglements and less resistance to flow, both of which contribute to lower viscosity. 62 Moreover, the smaller particle size can lead to lower viscosity. 63…”
Section: Resultsmentioning
confidence: 99%
“…Weaker hydrogen bonding interactions may result in fewer molecular entanglements and less resistance to flow, both of which contribute to lower viscosity. 62 Moreover, the smaller particle size can lead to lower viscosity. 63…”
Section: Resultsmentioning
confidence: 99%
“…The shear-thinning behavior observed fitted properly the power-law model included in Equation (5): where and are the consistency and flow indices, respectively. Once more, the stiffer samples generated when decreasing pH yielded higher values of the consistency index, whereas the flow index values close to 0 (see inset Figure 6 b) demonstrate poplar CNFs to possess an extremely pronounced shear-thinning behavior [ 69 , 70 ]. Nonetheless, the extreme toughness exhibited by the pH 1 CNF did not allow a proper fit to be obtained as a consequence of the expulsion of the sample during the test.…”
Section: Resultsmentioning
confidence: 99%
“…Oscillatory assays were also carried out on the CMC/EO sample (Figure 5b,c). Two different approaches were studied to record the corresponding modulus: (1) for a fixed strain, the oscillation frequency was changed (Figure 5b), and (2) at a fixed frequency (0.01 Hz), the shear stress was changed (Figure 5c) [43]. The results indicated that from the frequency of 0.1 Hz, the storage moduli could not be determined, as verified in Figure 5b.…”
Section: Characterization Of Cmc/eo Structurementioning
confidence: 95%
“…In the flow mode, controlled rate flow tests were performed with a shear rate (ẏ) in the range of 0.03 to 1000 s −1 for 180 s to determine the shear stress (т) and viscosity (ƞ). In the oscillation mode, viscoelastic behavior was studied with shear stress in the range of 0.07 to 1000 Pa and a frequency of 0.01 Hz to analyze the storage modulus (G′) and loss modulus (G″) [43]. The frequency value was selected by measuring G′ and G″ parameters at frequencies ranging from 0.01 to 1.0 Hz and applying a chosen stress value, allowing measurements within the linear viscoelastic region.…”
Section: Production and Characterization Of Cmc/eo Structurementioning
confidence: 99%